Educational Opportunities of Children in Poverty - Anke Schöb (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
In this paper, I use data from the German Socio-Economic Panel (GSOEP) to investigate whether and how a German youth' s choice of secondary school (Hauptschule, Realschule, Gymnasium) varies with the timing and duration of poverty experienced in childhood. To investigate what role the timing of poverty plays, I examine the correlation between educational choices and the poverty status of each child' s household in the three years preceding the educational decision to be analysed. Not surprisingly, persistently poor youth are less likely to choose higher educational trajectories.
Keywords: 330; Bildungschancen; Armut; Haushaltseinkommen; Kinder; Jugendliche; Schule; Deutschland